Democratic National Convention Vice Presidential Straw Ballot (1976)
This document is a July 12, 1976 notice and straw ballot distributed by NBC News to delegates at the Democratic National Convention. It explains that NBC is conducting three days of secret straw polling (white, red, and blue ballots) to gauge delegates' preferences for a vice presidential running mate prior to Governor Jimmy Carter's official selection. The ballot asks delegates to indicate their first, second, and last choices among listed candidates—including Senators Church, Glenn, Jackson, Mondale, Muskie, Stevenson, Congressman Udall, and others—and to submit the ballot in NBC collection boxes. Results of each day's straw vote were to be reported on NBC television and radio broadcasts from the convention hall.